Empowerment Communication in the Corporate Social Responsibility Program in Rural Areas - Sugito, Toto; Windiasih, Rili; Prastiyanti, Shinta; Sulaiman, Adhi Iman (Technium Sustainability, 2022)
Empowerment communication in the Corporate Social Responsibility program in rural areas is important for designing and implementing community empowerment with the support of its program. The research uses a case study method with data collection through in-depth interviews, Focus Group Discussions (FGD), documentation, and participant observation. The selection of research informants through purposive sampling, namely the village government, members and administrators of the Farmer Women’s Group (FWG), facilitators and extension workers of CSR programs, activists, and community empowerment activists. The research location is in the sub-District of Maos, Cilacap Regency, Central Java Province, Indonesia. Data analysis using triangulation and data verification. The results show (1) Community empowerment requires support and participation from various parties such as the woman farmers group, extension workers and facilitators as the main actors, the government with its policies and budgets, then the private sector or companies with their CSR programs. (2) Participatory communication is the key to success in designing and implementing empowerment with CSR programs. (3) Facilitators, extension workers, and village heads carry out harmonious dialogical communication that needs to be maintained for cooperation and to maintain cohesiveness in implementing the program.